IL-6 and hsCRP predict cardiovascular mortality in patients with heart failure with preserved ejection fraction - Berger, Martin; März, Winfried; Niessner, Alexander; Delgado Gonzales de Kleber, Graciela; Kleber, Marcus E.; Scharnagl, Hubert; Marx, Nikolaus; Schuett, Katharina (ESC heart failure, 2024)
Aims Inflammation accompanies heart failure (HF) and elevated levels of inflammatory biomarkers are linked to new onset of HF. However, whether the prognostic relevance of inflammatory biomarkers is different in HF with reduced (HFrEF) and preserved ejection fraction (HFpEF) is unclear. The aim of the current study is to explore the role of inflammation on the mortality risk in patients with HF. Methods We analysed interleukin-6 and hsCRP levels by ELISA and immunonephelometry, respectively, in HFpEF and HFrEF patients referred for coronary angiography and assessed the prognostic value in the Ludwigshafen Risk and Cardiovascular Health (LURIC) study. Results HF was present in 1086 patients (N = 506 HFpEF; N = 580 HFrEF; mean age 65 ± 10 years; 28% female). Increasing IL-6 levels were significantly associated with increased CV mortality in HFpEF [1.5 (95% CI: 1.1-2.2), P = 0.018] but not HFrEF [HR 1.3 (95% CI: 1.0-1.7), P = 0.06] patients. High-sensitive CRP followed a similar pattern but failed to reach statistical significance after full-adjustment (HFpEF: HR 1.4 95%C I: 1.0-2.0; P = 0.065; HFrEF HR: 1.0 95% CI: 0.7-1.3; P = 0.800). Interaction analysis in patients stratified by IL-6 and N terminal pro brain natriuretic peptide (NT-proBNP) above and below the median revealed a stepwise increase in CV-mortality in HFpEF (P = 0.036) but not HFrEF patients (P = 0.220). To investigate the relationship between IL-6 and NT-proBNP, we assessed the genetic IL6-Receptor variant p.Asp358Ala (rs2228145) which is linked to impaired IL-6 receptor signalling. Homozygous carriers with HFpEF but not HFrEF exhibited significantly lower NT-pro-BNP levels compared with wildtype carriers (HFpEF 779 pg/mL ± 787 vs. 1180 pg/ mL ± 1532; P = 0.008; HFrEF 2289 pg/ mL ± 3439 vs. 2326 pg/ mL ± 3386; P = 0.94), raising the hypothesis that IL-6 signalling may play a pathophysiological role in HFpEF. Conclusions These data suggest a predictive value of elevated IL-6 for CV-mortality in HFpEF but not in HFrEF patients.